f(x) = 5x^2 - 4x
g(x) = 5x + 1
Therefore f - g = 5x^2 - 4x - (5x + 1)
= 5x^2 - 4x - 5x -1
= 5x^2 -9x - 1
Hope it helps :)
Answer:
0-5
Step-by-step explanation:
1 if theres 5 topping. 2 if there are 10 toppings. 3 if 15. 4 if 20. 5 if 25.
Answer:
the possible outcomes are :
- one (1)
- two (2)
- three (3)
- four (4)
- five (5)
- six (6)
Answer: 8+18W
Step-by-step explanation:
1. First multiply the 4 by 2, equalling 8.
2. Then multiply the 9W by 2, equalling 18W.
3. 8 and 18W are unlike terms, so they can not be added together.
4. The answer would stay as 8+18W.